Comparative study of high intensity ultrasound effects on food proteins functionality - Arzeni, Carolina (2012)
The objective of this work was to comparatively explore the impact of high intensity ultrasound (HIUS) on the functionality of some of the most used food proteins at the industrial level: whey protein concentrate (WPC), soy protein isolate (500E) and egg white protein (EW).10% w/w solutions at pH 6.5?7.1 were treated with HIUS for 20 min, in an ultrasonic processor. The operating conditions were: 20 kHz, 4.27 ± 0.71 W and 20% of amplitude.Before and after the HIUS treatment, the size of protein particles was measured by static light scattering. The amount of sulfhydryl groups was determined with Ellman?s reagent and the surface hydrophobicity by a fluorescence technique.The effects of HIUS on samples viscosity were determined. The evolution of the elastic (G′) and viscous (G″) moduli as well as tan δ were registered upon time and temperature in a controlled stress rheometer.In general, HIUS promoted a decrease in the consistency index of all protein solutions, mainly of soybean isolate. The gelation performance of EW was not modified by HIUS. However, WPC presented a higher elastic character, but 500E did not show changes upon heating, as it was already denatured before HIUS treatment. The size of aggregates suffered an overall reduction for WPC and 500E, but a slight increase for EW. Sulfhydryl content was unchanged for all proteins after HIUS application but surface hydrophobicity was greatly increased after treatment for all proteins. HIUS affected the studied functional properties differently depending on the size and nature of the protein. This technology could be used to obtain improved functional properties in some protein samples.